2016
DOI: 10.1590/1806-9282.62.01.72
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen signaling in the proliferative endometrium: implications in endometriosis

Abstract: suMMaryEven though the physiological role of estrogen in the female reproductive cycle and endometrial proliferative phase is well established, the signaling pathways by which estrogen exerts its action in the endometrial tissue are still little known. In this regard, advancements in cell culture techniques and maintenance of endometrial cells in cultures enabled the discovery of new signaling mechanisms activated by estrogen in the normal endometrium and in endometriosis. This review aims to present the recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In the normal human endometrium, eNOS is regulated by estrogen and progesterone (Han et al, 2005;Khorram et al, 2009;Silva et al, 2016) and is expressed in the glandular and endometrial microvascular epithelium during the luteal phase (Cameron and Campbell et al, 1998). Therefore, synthesis of adequate NO levels is required for proper hormonal signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal human endometrium, eNOS is regulated by estrogen and progesterone (Han et al, 2005;Khorram et al, 2009;Silva et al, 2016) and is expressed in the glandular and endometrial microvascular epithelium during the luteal phase (Cameron and Campbell et al, 1998). Therefore, synthesis of adequate NO levels is required for proper hormonal signaling.…”
Section: Discussionmentioning
confidence: 99%
“…As it pertains to the uterus, estrogen binds to estrogen receptors (ER; alpha and beta) in the cytoplasm or nucleus of endometrial glandular and epithelial stromal cells. The resulting E2-ER complex can then directly interact with the promoter regions of specific sequences of DNA related to the G1 phase of the cell cycle and induce mitotic proliferation by regulating cyclins, cyclin-dependent kinases (cdk), and cyclin-dependent kinase inhibitors [3]. One of these cyclins includes cyclin E, which increases in concentration during the endometrial proliferative phase and in response to estrogen signaling.…”
Section: The Proliferative Phasementioning
confidence: 99%
“…Along with cdk2, cyclin E is believed to be the rate-limiting activator of G1 to S phase [4]. Other cyclins that are directly regulated by binding of the E2-ER complex include cyclin B1 and cyclin D1 [3]. Throughout the ovarian follicular phase, as serum estrogen levels continue to rise in response to folliculogenesis, the transcription of cell cycle-related genes in the endometrial tissue increases.…”
Section: The Proliferative Phasementioning
confidence: 99%
“…5,6 Oestrogen fuels the cell proliferation, promotes inflammation and inhibits apoptosis, and it is regarded as one of the factors that promotes the development of endometriosis. [7][8][9] Studies found that aromatase and oestrogen kept high level in endometriosis tissues and survived the cells in ectopic locations. 10,11 Furthermore, other studies have reported the aberrant level of EMT is present in endometriosis and oestrogen induces cell proliferation, invasion, migration and EMT-related markers in both normal and endometriotic epithelial cells.…”
Section: Introductionmentioning
confidence: 99%